Entrepreneurship Development Model At Islamic Boarding School - Nurul Badriyah; Setyo Tri Wahyudi; Mokhamad Nur; Kartika Sari; Rihana Sofie Nabella; Radeetha (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
Community partnership programs have been implemented in various regions in Indonesia, one of which is Santripeneur. This program aims to generate new entrepreneurs and produce superior products for Islamic boarding schools, which became known as the One Pesantren One Product program (OPOP). One of the Islamic boarding schools in Malang that has implemented the OPOP program is the An-Nashr Wajak Islamic Boarding School through the cultivation of chicken and catfish farms using qualitative research methods to analyze the impact of implementing OPOP implementation and assisting Islamic boarding schools in strengthening the vision in running a business according to the potential of the Islamic boarding schoolThe study results indicate that Islamic boarding schools' role is learning, disseminating religious knowledge, increasing students' creative attitudes, increasing entrepreneurial attitudes and advancing the economy of students, the community through livestock business is one of the roles of An-Nasr Islamic Boarding School in the socio-economic field.